Effectiveness of Citronella and Basil Essential Oil Spray as Repellents against Aedes aegypti Mosquitoes: Efektivitas Spray Minyak Atsiri Serai Wangi Dan Daun Kemangi Sebagai Repellent Nyamuk Aedes Aegypti - Qomariyah, Laila Nurul; Kusumo, Djati Wulan; Pratiwi, Elasari Dwi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: In 2023, Dengue Fever cases in Indonesia reached 35,694 cases from January to May. Dengue Fever is caused by the bite of Aedes aegypti mosquitoes. Mosquito control efforts have been widely conducted, including the use of chemical insecticides. The use of chemical insecticides can lead to environmental contamination and cause skin irritation. An alternative approach that can be taken is to use natural insecticides. One of the natural insecticides that can be used as a repellent is citronella and basil essential oils. Citronella and basil essential oils contain geraniol and citronellal, which can cause mortality in mosquitoes. This study intends to evaluate the effectiveness of a spray mixture of basil leaves and citronella essential oil as a mosquito repellent. Materials and Methods: Aedes aegypti mosquitoes, basil leaf essential oil, citronella essential oil, propylene glycol, glycerin, butylated hydroxytoluena and etanol 96% v/v. Subsequently, an evaluation of physical properties was conducted, including organoleptic testing, pH, and viscosity evaluation, as well as irritation and repellent activity test. Results: The spray formulations in the control and F1 are clear in color, while F2 and F3 are clear with a slightly yellowish hue. The scent produced has the characteristic smell of citronella. The pH and viscosity tests resulted in pH values consistent with the skin's pH range of 4.5-7 and viscosity within the range of 1-1000 Cp. The spray formulation did not irritate after 48 hours of observation. The results of the effectiveness test indicate that F2 can protect against mosquito bites for 1 hour, while F3 can protect for 3 hours. Conclusion: Citronella essential oil and basil leaves are effective as a repellent for the Aedes aegypti mosquito for 3 hours of use in concentration 15%.